Heat Transfer Management of Thermal and Electronics Systems using Convective-Radiative Porous Fins with Thermal Contact Resistance and Diabatic Tip - Joy Nneka Ojuro; Gbeminiyi Musibau Sobamowo; Antonio Marcos de Oliveira Siqueira (The Journal of Engineering and Exact Sciences)
The miniaturization of electronics, electrical, thermal, mechanical and optical devices and systems calls for increasing demand for efficient cooling systems with higher thermal efficiency. The use of passive mode of cooling using fins has provided unprecedented results. However, the previous transient analyses of the extended surfaces have been done without proper considerations of the imperfect contact between the fin base and the prime surface. Also, the tip of the passive device has been assumed to be adiabatic. However, the present article explores the significances of thermal contact resistance and diabatic tip on the transient thermal response of straight fin with temperature-dependent thermal conductivity and magnetic field under radiative-convective conditions. The nonlinear model is analyzed numerically using generalized Integral Transform Techniques and the numerical results are verified by the exact solution for the linear thermal model. The parametric explorations reveal that the adimensional local temperature in the conductive-radiative fin increases when the conductive-convective, conductive-radiative and magnetic field parameters increase. However, under the assumption of perfect thermal contact between the prime surface and the base of the fin, the adimensional temperature in the fin will decrease as the conductive-convective, conductive-radiative and magnetic field parameters increase. The fin temperature is significantly affected by the Biot numbers under the comparably low values of the conductive-convective, conductive-radiative, magnetic field and thermal conductivity parameters. The effects of the fin thermal conductivity parameter along the fin length depend on the respective values of thermal contact Biot number at the base of the fin and the end cooling Biot number at the tip of the fin. When the thermal conductivity parameter is amplified, the fin adimensional temperature increases when thermal contact Biot number at the base of the fin is zero and the end cooling Biot number at the tip of the fin is very large. This study will help in accurate analysis and design of heat sinks and passive devices for heat transfer enhancement for thermal and electronic systems.